2018
DOI: 10.1002/fsn3.772
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of yogurt and exercise in healthy adults: Implications for biomarkers of depression and cardiovascular diseases

Abstract: Several studies have reported individual benefits of yogurt and exercise on health; however, their combined effects remain unclear. Twenty‐four healthy individuals participated in the study and were randomly assigned to the following four groups: control, yogurt, exercise, and combination. The participants consumed yogurt and exercised for 2 weeks, and we examined the combined effects of yogurt and exercise on physiological biomarkers. Individually, yogurt and exercise did not exert a significant effect on bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We also summarized the dosage, strain, and species of probiotics. Our systematic review and meta-analysis revealed that probiotic supplementation is a non-invasive therapy that can be used routinely in prenatal and postnatal women and newborns to improve the physical and mental well-being and microbiota of newborns [ 53 ]. Probiotics, prebiotics and synbiotics supplementation reduced prenatal depression [ 54 ], newborn abdominal colic [ 45 , 55 ] and regurgitation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also summarized the dosage, strain, and species of probiotics. Our systematic review and meta-analysis revealed that probiotic supplementation is a non-invasive therapy that can be used routinely in prenatal and postnatal women and newborns to improve the physical and mental well-being and microbiota of newborns [ 53 ]. Probiotics, prebiotics and synbiotics supplementation reduced prenatal depression [ 54 ], newborn abdominal colic [ 45 , 55 ] and regurgitation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a cohort of 14,539 men and women during more than 9 years from the SUN (Seguimiento Universidad de Navarra) project observed that whole-fat yogurt, but not low fat, was related to a decreased risk of depression in women, once again supporting the relevance of the entire food matrix in the benefits of a food product [ 164 ]. Moreover, the combination of yogurt plus exercise in healthy individuals led to greater increases in serotonin levels and reductions in triglyceride and high-sensitivity C-reactive protein (CRP) levels, relative to those observed for yogurt or exercise alone, demonstrating the synergic role of different lifestyle factors in the prevention of depression and inflammatory conditions [ 165 ].…”
Section: Translational Opportunities: Clinical Management Of Mdd Thro...mentioning
confidence: 99%
“…Furthermore, a randomized, double-blind, placebo-controlled trial of 82 patients with depression showed that the consumption of Lacticaseibacillus paracasei strain Shirota for 9 weeks improved depression-like behaviors and ameliorated constipation of patients, which was related to upregulate the beneficial Adlercreutzia , Megasphaera and Veillonella levels [ 101 ]. In a randomized trial of 24 healthy volunteers, consumption of yogurt twice daily after lunch and dinner did not significantly change biomarker levels of depression, but when the participants regularly consumed yogurt and daily exercised, the level of serotonin increased [ 102 ]. Additionally, a meta-analysis of 36 clinical trials including 2788 participants showed that the higher flavonoid consumption improved depressive symptoms (Mean difference = −1.65; 95% CI, −2.54, −0.77) [ 103 ].…”
Section: Depressionmentioning
confidence: 99%